Reminding State Owned Enterprises (BUMN) Management Using the Principle of ’Business Judgment Rule’: A Preliminary Note - Teuku Syahrul Ansari (Budapest International Research and Critics University, 2019)
This paper explains that the development of BUMN (state owned enterprises) as a corporation that carries out social and business missions is facing constitutional juridical problems and facing the challenges of globalization. Factually, at this time legal development cannot be separated from the influence of globalization. Globalization in the economic field has affected various fields of the business sector in the world. This globalization is followed by the globalization of law, which causes substantially various laws and agreements to spread across national borders, which causes the merging of legal principles (especially in the economic sector) from one country to another . For Indonesia, the logical consequence of this development is the demand to harmonize the principles of economic law in Indonesia, with the principles of economic law in the international world. Without harmonization, Indonesia can be ostracized in international business activities, because there is no certainty for legal protection for business and investment activities that are commonly carried out globally. The Constitutional Court in case number 48 / PUU-XI / 2013 and case No. 62 / PUU-X1 / 2013 dated May 22, 2013 decided that management BUMN must use the principle of Business Jugment Rule. In the ruling, it was also stated that state owned finances were state finances. As a result, this ruling brings legal certainty about the position of finance of BUMN.